PENGARUH HARGA POKOK PRODUKSI TERHADAP PENETAPAN HARGA JUAL PADA CV MAJUJAYA - Widi Winarso (Universitas Bina Sarana Informatika, 2014)
This study aims to: 1). to know the development cost of production t-shirt CV.Maju Jaya. from years 2007-2011, 2). to determine the selling price of the product development t-shirts CV. Maju Jaya from years 2007-2011, 3). to determine how much influence the Cost of Production Against Selling Price Determination in CV. Maju Jaya. The method used in this research is descriptive method of analysis with a case quantitative, data collection technique through observation, interviews, documentation and literature containing data on the cost of product and selling price as well as other support during the period 2007-2011 which is based on the company. The variables were tested for the cost of product as the independent variable (X) and the selling price as the dependent varable (Y). Analyzer applied is simple regression test with measurenment scale of ratio. Then to find out how big and strong influence of one or more variables use correlation coefficients, and the coefficient of determination to find out the extent of the influence of the variable X to variable Y in the form of percentage. While the test is used to test the hypothesis of t, i.e., to determine the level of significance between the independent variable (X) the cost of goods production of the dependent variable (Y) is the selling price. The conclusions of this study, H0 is rejected, which means that the price accepted H1 staple production influence significantly to selling price. While the effect of the cost of production to the selling price by 99.8% and 0.04% are influenced by factors other than the cost of production, for example, the increase in non-production costs, marketing costs and others. So it can be concluded that the cost of production significantly influence the selling price which means that if the cost of production rises then the selling price will rise anyway Key Word : Cost of Goods Sold (COGS), Selling Price.